Urbanization in Asia and the far east - Hauser, Philip M.(ed.) (Calcutta, 1957)
This volume is organized into two parts. First, as Part I, are ented the Summary Report of the General Rapporteur, and the clusions of the Seminar. Next, as Part II, are presented the papers pared for the Seminar which refer to the ECAFE Region as a ole or to broad problems affecting many of the countries in the on. Unfortunately the individual country statements prepared ome of the ECAFE countries are, because of space limitations, not published. Much of the specific data and general import of the statements, however, has been embodied into the Summary Report and the Conclusions of the Seminar and in the general papers i Part II. The same is true of an extensive preliminary report on the his ve Relation of Physical Planning to Urbanization, submitted by Bureau of Social Affairs as a background document.
Keywords: Urbanization